Effect of Self-Attribution Bias on Investment in the Rwandan Stock Market (Global Journal of Management and Business Research, 2018)
The main objective of this study was to establish the effect of self-attribution bias on investment in the Rwanda Stock Exchange The study used cross-sectional descriptive survey research design to ascertain and establish the effect of behavioural biases on investment in the Rwanda stock exchange The target population comprised of 13 543 individual group investors at the Rwanda Stock Exchange Random sampling was used where the targeted population was individual investors to finally yield a sample size of 374 respondents A questionnaire was used to collect the primary data A pilot test was undertaken by carrying out a small scale trial run of the research instrument Data analysis involved the use of descriptive and inferential statistics A Linear regression model was used to predict the probability of different possibility outcomes of dependent variables helping to predict the probability of an investor to invest in RSE The results confirmed that there was a significant positive linear relationship between self-attribution biasand Investment in Rwanda stock market The study also concluded that most investors suffered from self-attribution bias in investment in stock markets The study recommends that investors should be keen to identify such bias to increase their rationality in stock trading
Keywords: self-attribution bias; investment; rwanda; stock; exchange